Role of Procedural Justice and Organizational Trust on Organizational Citizenship Behavior among IT Employees - et al., Navin Kumar Koodamara (International Journal of Advanced Science and Technology, 2019)
The purpose of this research is to find the influence of Procedural Justice (PJ) and Organizational Trust (OT) on Organizational Citizenship behaviour (OCB). The organizational citizenship behaviour has three sub-components such as Helping Behavior (HB), Sportsmanship and Civic Virtue (CV). Procedural justice is considered as a mode to gain the trust between the organization and the employees by stepping towards the approaches that help to build and maintain trust. From the literature, it is inferred that both sales representatives and sales managers the cooperation among organizational trust, Procedural Justice and Organizational Citizenship Behavior is highly related. In the present study, there are a total 185 respondents from the various retail sector and the researcher mainly focused on to find out the relationship between Procedural Justice, Trust and Organizational Citizenship Behavior of Sales managers of the various retail sector. From the regression test it can be inferred that there is a high correlation between Procedural justices and Organizational Citizenship Behavior, and between the Organizational trust and Organizational Citizenship Behavior. Also, Regression test was done to check the relationship of procedural justice and organizational trust with the three elements of the organizational Citizenship behaviour individually. The result obtained from the regression test explains that there is a high correlation between the Procedural justice and helping behaviour, moderate correlation between the Procedural justice and sportsmanship and finally, good correlation between the Procedural justice and Civic virtue. Also, from the test, it is inferred that there is a good correlation between the Trust and helping behaviour, moderate correlation between the Trust and sportsmanship and a good correlation between the Trust and Civic virtue.